Filmowe wcielenia Krzysztofa Kamila Baczyńskiego - Szpulak, Andrzej (Przestrzenie Teorii, 2019)
Szpulak Andrzej, Filmowe wcielenia Krzysztofa Kamila Baczyńskiego [Film Incarnations of Krzysztof Kamil Baczyński]. „Przestrzenie Teorii” 32. Poznań 2019, Adam Mickiewicz University Press, pp. 301–322. ISSN 1644-6763. DOI 10.14746/pt.2019.32.16. The text concerns two film biographies of Krzysztof Kamil Baczyński, an outstanding and legendary poet of the Second World War killed in 1944 during the Warsaw Uprising. The films Fourth Day by Ludmiła Niedbalska (1984) and Baczyński by Konrad Piwowarski (2013) were subject to a comparative analysis. It covered genaelogical issues, the poet’s biography and a presentation of his work. The analysis shows the extreme difference in creative concepts, and thus the various possibilities that the biographical film faces.